2001
DOI: 10.1103/physrevlett.87.263401
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of Charge-Density Fluctuations in Metal Clusters: Suppression of the Ionization Channel

Abstract: The fluctuations in the electronic charge density of metallic clusters in response to an approaching electron suppress the single-ionization channel. This conclusion is made on the basis of numerical calculations for the total ionization cross sections using the random-phase approximation with exchange to describe the particle-hole (de)excitations. The general trends can be understood by means of the Thomas-Fermi model. The present theory explains, for the first time, the behavior of the measured total ionizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Furthermore, we pointed out the need for further experimental investigations to separate the exchange-driven contributions to screening and to obtain full information on the angular and energy dependence of the screening of the electron-electron interaction in the valence band of fullerenes. As shown in [8], much of these findings are also valid for other nano-sized systems, such as metal clusters.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Furthermore, we pointed out the need for further experimental investigations to separate the exchange-driven contributions to screening and to obtain full information on the angular and energy dependence of the screening of the electron-electron interaction in the valence band of fullerenes. As shown in [8], much of these findings are also valid for other nano-sized systems, such as metal clusters.…”
Section: Discussionmentioning
confidence: 56%
“…A posteriori, we will find that this approach is justified for moderately large systems, such as C 60 , due to the fact that screening is substantial. Within RPAE, the matrix elements Tðk 1 k 2 , k 0 Þ are given by the equation [8]:…”
mentioning
confidence: 99%
“…Density functional calculations (DFT) with the local density approximation (without RPA) as well as Hartree-Fock calculations failed to reproduce the excitation probability as a function of the excitation energy [15][16][17]. Thus an obvious step to remedy (or at least to improve) this situation is to evaluate the removal probability within RPA.…”
Section: Excitations In Finite Systems: Role Of the Electron-electronmentioning
confidence: 99%
“…In contrast, within DFT-LDA exchange and correlation effects are described in an approximate way through the employed exchange and correlation functional. This advantage of the HF comes of the expense of evaluating the expectation value of a large number of non-local potentials (Fock terms) [17,18]. It turns out that the numerical problems arising from the non-locality of the potentials can be circumvented by utilizing the variable-phase method (VPM).…”
Section: Formal Developmentmentioning
confidence: 99%
“…Due to its icosahedral symmetry (resembling a soccer ball [1]), one would intuitively expect a minor impact of orientation effects on the underlying mechanisms. And indeed, many laser and collision induced phenomena have been explained succesfully within the spherical jellium approximation [6][7][8][9][10][11][12][13][14] or the infinitely conducting sphere model [15,16].However, Gutierrez et al [17] found, that the conductance across a C 60 junction between two carbon nanotubes changes with the orientation of the molecule with respect to the tubes over several orders of magnitude. Furthermore, it has been observed experimentally [18], that the fusion cross section in fullerene-fullerene collisions is several orders of magnitude smaller than that of the expected geometrical one.…”
mentioning
confidence: 99%